Analytical Derivation of the q-Factor for Slender Masonry Structures Under Out-of-Plane Seismic Action - Simona Coccia (Buildings)
Slender masonry structures, in the absence of disintegration phenomena, can be idealized as rigid bodies subjected to seismic excitation. In this study, a closed-form expression for the behavior factor (q-factor) associated with overturning collapse under out-of-plane seismic loading is derived. The analysis considers five-step pulse seismic inputs. In the proposed approach, valid for slender masonry structures, sliding failure is neglected, and collapse is assumed to occur when, at the end of the seismic excitation, the rotation of the structure reaches a value equal to its slenderness. Based on this criterion, it is possible to derive a formulation for the q-factor as a function of a dimensionless parameter that combines the geometric characteristics of the slender structure and the period of the applied accelerogram. To validate the proposed formulation, a comparative analysis is conducted against the results obtained from a numerical integration of the motion equation using a set of 20 natural accelerograms recorded in Italy. The characteristic period of each accelerogram is evaluated through different methodologies, with the aim of identifying the most suitable approach for application in simplified seismic assessment procedures.